TETO Surabaya’s Role in Promoting Indonesian Labor Migration - Khoiriyah, Nur; Hakim, Fathoni (Universitas Airlangga, 2025)
The rapid advancement of technology has dissolved geographical boundaries, integrating economic, political, and cultural dimensions. This has intensified societal connectivity through increased economic productivity and cultural exchanges, including labor migration. Taiwan, currently grappling with a labor crisis driven by declining birth rates and an aging population, has become a key destination for Prospective Indonesian Migrant Workers (CPMI). The dependency ratio between the non-productive population (over 65 years) and the productive population is rising, with the elderly expected to make up 19.8% of the population by 2025, posing significant challenges to Taiwan’s productivity and economic growth. Conversely, remittances from Indonesian Migrant Workers (IMW) represent a vital opportunity for Indonesia’s economic growth and serve as a strategic approach to addressing labor market disparities. This study uses a descriptive qualitative methodology to analyze the role of Taipei Economic and Trade Office (TETO) Surabaya in facilitating international labor migration from eastern Indonesia to Taiwan, drawing on secondary data. Applying Lee’s push and pull theory (1966), the study concludes that through TETO Surabaya’s guidance and support, factors such as push-pull dynamics, intervening obstacles, and personal factors have ultimately promoted IMWs migration to Taiwan. Keywords: CPMI; Eastern Indonesia; International Labor Migration; Push and Pull Factors; TETO Surabaya.